Financial Level Analysis of Female Micro Entrepreneur - Sari, Maheni Ika; Suharto, Akhmad; Supeni, Retno Endah (Budapest International Research and Critics University, 2022)
The condition of female micro entrpreneur in Bondowoso Nangkaan Market currently still has limitations with various problems. These limitations include capital, lack of knowledge in financial management, financial management skills, low financial and financial behavior, limited access to information and technology, and the limited scope of the market which is still a limiting factor for the SME space. This study aims to determine the level of financial literacy based on financial knowledge, financial behavior, financial skills, financial attitude, and financial performance. The research design used in this study is quantitative research because it uses data in the form of numbers in descriptive statistical analysis. The population in this study is the economic actors of SME Women in the Nangkaan Market Bondowoso Regency with a sample of 68 SME of Women. The results of this study indicate that based on financial knowledge, financial behavior, financial attitude, financial skills, and financial performance are classified as low because they are under 60%. The high level of financial literacy is believed to be able to improve welfare because by increasing the level of financial literacy, female micro entrpreneur economic actors can make financial decisions better so that business financial planning becomes more optimal, which in turn can improve welfare.The results of this study indicate that based on the five variables that use the financial literacy rate of female SME are in the middle category.